Yoga sebagai Terapi Komplementer dalam Manajemen ADHD: Tinjauan Literatur - Ni Putu Nirmala Evelyn; Ni Nyoman Mestri Agustini; Ni Putu Kaori Prajaniti; Putu Rania Apta Savitri; Kadek Wanda Pratiwi Adibrata (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2026)
Introduction: Attention-Deficit/Hyperactivity Disorder (ADHD) is the most common neurodevelopmental disorder in children, characterized by symptoms of inattention, hyperactivity and impulsive behaviour. Pharmacological therapy is often used as the primary intervention for ADHD, but it has limitations, particularly regarding side effects. Therefore, complementary approaches such as yoga are increasingly attracting research interest. This study aims to critically evaluate the effectiveness of yoga as a complementary therapy in the management of ADHD in children. Method: This study is a literature review. Article searches were conducted in the PubMed, Google Scholar, and ScienceDirect databases using the keywords “Yoga” AND “ADHD” OR “Attention-Deficit/Hyperactivity Disorder” AND “Children” within year 2015–2025. Included articles were experimental studies involving participants aged 3–17 years who exhibited symptoms or had a diagnosis of ADHD. A total of nine articles met the inclusion criteria. Discussion: Yoga was found to have positive effects in reducing ADHD symptoms, such as improved attention, better emotional regulation, and reduced hyperactivity. Additionally, yoga is generally well-tolerated by children due to its minimal side effects. Conclusion: Yoga shows potential as a safe and effective complementary therapy for managing ADHD in children. However, its effectiveness may be influenced by various factors. Further research with stronger study designs and larger populations is needed to support these findings. Keywords: Yoga, ADHD, children, complementary therapy